The concept of flexibility in the formation of contemporary biological spaces - Ghanbari, Taban; Soltani, Mahsa (Revista de la Universidad del Zulia, 2020)
Flexibility in architectural spaces makes it possible to adjust the living conditions associated with human settlements and adapt the residential unit to human behavior. Today, due to the lack of a correct statement about the proper placement of spaces, biologic neighborhoods in relation to geographic location and the neglect of the true concept of comfort in modern buildings, seems necessary to provide appropriate solutions to this problem. What is the concept of flexibility and how to create and achieve solutions for the reconciliation of the human environment in the climate of own habitat? All of this research seeks to provide a solution to the creative design of flexible spaces, with goals such as: improving and increasing the performance of residential spaces, developing creative design solutions in residential spaces, introducing theoretical foundations and criteria for flexible spaces, and taking advantage of in today's design of housing. The study of theoretical concepts of flexible spaces will help residents to create comfort in the living space of contemporary buildings. This research proposes, through deductive reasoning, appropriate solutions to the positive effects of physical, functional, social and functional characteristics, on increasing the comfort of living in resident settlements. This research is of qualitative and descriptive-analytic method for elaboration of the issue of flexibility and promotion of biological comfort in contemporary habitat. In the discussion of theoretical foundations, a library research has been used including specialized sites, books and scientific articles that use Results and data aggregation can be found in effective physical solutions appropriate to the conditions of the construction of contemporary buildings in Iran.